2022
DOI: 10.1039/d2ra01929a
|View full text |Cite
|
Sign up to set email alerts
|

Potential antimicrobial, antidiabetic, catalytic, antioxidant and ROS/RNS inhibitory activities of Silybum marianum mediated biosynthesized copper oxide nanoparticles

Abstract: Use of medicinal plants for the biosynthesis of nanoparticles offers several advantages over other synthesis approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…The results showed that synthetic CuNPs had a modest level of inhibition for the -amylase enzymes, which is comparable to the sample's percent inhibition. At 1000 µg/ml concentration, CuNPs inhibited the -amylase enzyme by 76.03±1.14 %, which is roughly comparable to the other report of Silybum marianum copper nanoparticles [26]. Our research suggested that the LACuNPs have a significant capacity for enzyme inhibition.…”
Section: Discussionsupporting
confidence: 87%
“…The results showed that synthetic CuNPs had a modest level of inhibition for the -amylase enzymes, which is comparable to the sample's percent inhibition. At 1000 µg/ml concentration, CuNPs inhibited the -amylase enzyme by 76.03±1.14 %, which is roughly comparable to the other report of Silybum marianum copper nanoparticles [26]. Our research suggested that the LACuNPs have a significant capacity for enzyme inhibition.…”
Section: Discussionsupporting
confidence: 87%
“…Nanotechnology has been recently exploited as a tool to investigate unilluminated approaches in many ways, such as artificial implants, imaging, targeted drug delivery, sensing and gene-delivery systems [ 1 ]. Generally, nanoparticles [ 2 ] constitute 20–15,000 atoms, their size is smaller than 100 nanometers, and they exist in a realm that bestrides the Newtonian and quantum scales. Nanoparticles can be generated from various materials in numerous shapes, such as wires, spheres, tubes, and rods [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation reported that silver NPs synthesized from Phagnalon niveum methanol extract demonstrated antidiabetic activity by reducing the blood glucose level and also reduced the body weight of rats in 1 to 21 days [ 178 ]. Spherical shaped-CuO NPs synthesized from Silybum marianum seed extract displayed great enzymatic inhibitory activity against ureases, alpha-amylase, and lipases so it was concluded that they can act as antidiabetic agents [ 179 ]. ZnO NPs and Au NPs which are synthesized using Dicoma anomala and Eclipta alba , respectively, are good alternative sources for antidiabetic medicine [ 98 , 117 ].…”
Section: Application Of Asteraceae -Based Nanopart...mentioning
confidence: 99%